Proceedings of Topical Issues in International Political Geography - Bolgov, Radomir; Atnashev, Vadim; Gladkiy, Yury; Leete, Art; Tsyb, Alexey; Pogodin, Sergey; Znamenski, Andrei (Springer Geography, 2021)
XII, 476 p. 13 illus., 7 illus. in color.